Accessibility and active offer: Health care and social services in linguistic minority communities - Drolet, Marie; Bouchard, Pier; Savard, Jacinthe (University of Ottawa Press, 2017)
This edited volume examines language issues within the active offer of health and social services in francophone and anglophone minority communities. Action based, it will help shape the leaders of tomorrow. It is imperative that we train leaders who are able to intervene efficiently with service users and to support a better organization of the workplace. It is especially important to look at the many issues related to postsecondary training and human resources, such as recruiting and keeping these leading professionals. Accessibility and Active Offer thus combines theory and empirical data to help future professionals understand the workplace issues of accessibility and active offer of minority-language services. This English-language adaptation of Accessibilité et offre active features an additional chapter by Richard Bourhis on issues specific to Anglophone communities in Québec.

Vers une démarche concertée pour le renforcement de la recherche sur les langues officielles dans le secteur de la santé : bilan et pistes d’action - Vézina, Sylvain; Doiron Robichaud, Johannie (Bureau d’appui aux communautés de langue officielle de Santé Canada, 2011)
fs-ref-orig: Vézina, S. et Doiron Robichaud, J. (2011). Vers une démarche concertée pour le renforcement de la recherche sur les langues officielles dans le secteur de la santé : bilan et pistes d’action. Bureau d’appui aux communautés de langue officielle de Santé Canada. http://docplayer.fr/123792385-Vers-une-demarche-concertee-pour-le-renforcement-de-la-recherche-sur-les-langues-officielles-dans-le-secteur-de-la-sante-bilan-et-pistes-d-action.html fs-code-orig: Vézina-2011